Effectiveness of Acupuncture Therapy Combination of Ginger Patch on Changes in Pain Scale in Cases of Knee Pain in Tempak Village, Candimulyo District - Febiyasari, Eka; Badri, Sholichan; Prasetya, Hanung; Sasmita, Hanum (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Knee pain is a common complaint in the pre-elderly group and can be caused by various factors, such as osteoarthritis, strenuous physical activity, or degenerative processes. Knee pain management can be from pharmacological and non-pharmacological therapies, such as acupuncture and herbal administration. This study aims to determine the effectiveness of acupuncture therapy combined with the provision of patches (Ginger Patch) on changes in the pain scale in cases of knee pain. This study used a quasi-experimental research design with a nonequivalent control group design with a purposive sampling technique. The research subjects consisted of 32 pre-elderly people of females gender. Pain measurements were taken using the Numeric Rating Scale (NRS) before and after the intervention. The points used were EX LE-2 Heding, ST 36 Zusanli, LV 7 Xiaguan, and SP 6 Sanyinjiao. Pain measurement used the Numeric Rating Scale (NRS). The results of the Wilcoxon and Mann-Whitney tests showed a significant change in the pain scale in the experimental group compared to the control group (p<0.05). the combination of acupuncture and patch therapy (Ginger Patch) is more effective in changing the pain scale in cases of knee pain.